A visceral mycosis in farmed rainbow trout (Oncorhynchus mykiss) caused by Neopyrenochaeta submersa - Řehulka, Jiří; Kubátová, Alena; Hubka, Vit (Medical mycology case reports, 2023)
A mycotic infection manifesting as abdominal distension with free serous fluid accumulation in the coelomic cavity is documented in farmed rainbow trout. Histological examination using PAS and silver staining revealed the presence of numerous fungal hyphae in the spleen and gastrointestinal wall. The isolated fungus was sterile and identified by using phylogenetic analysis based on four loci as Neopyrenochaeta submersa. This is the first time this fungus has been reported as pathogen.